Universality for the Toda Algorithm to Compute the Largest Eigenvalue of a Random Matrix. Issue 3 (24th August 2017) - Deift, Percy; Trogdon, Thomas
Abstract: We prove universality for the fluctuations of the halting time for the Toda algorithm to compute the largest eigenvalue of real symmetric and complex Hermitian matrices. The proof relies on recent results on the statistics of the eigenvalues and eigenvectors of random matrices (such as delocalization, rigidity, and edge universality) in a crucial way.© 2017 Wiley Periodicals, Inc.